2008
DOI: 10.1208/s12249-008-9147-4
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size, Moisture, and Fluidization Variations Described by Indirect In-line Physical Measurements of Fluid Bed Granulation

Abstract: Abstract. The aim of this study was to evaluate an instrumentation system for a bench scale fluid bed granulator to determine the parameters expressing the changing conditions during the spraying phase of a fluid bed process. The study focused mainly on four in-line measurements (dependent variables): fluidization parameter (calculated by inlet air flow rate and rotor speed), pressure difference over the upper filters, pressure difference over the granules (lower filter), and temperature of the fluidizing mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Plitzko and Dietrich focussed on the in-line SFV detection of pellet agglomeration during Wurster coating [30], while SFV has recently been established for in-line particle size monitoring in fluidized bed granulation [27,[31][32][33][34][35][36]. The obtained SFV data improved the understanding of the impact of process variables by using model-based process control approaches, such as DoE, univariate and multivariate PLS.…”
Section: Introductionmentioning
confidence: 99%
“…Plitzko and Dietrich focussed on the in-line SFV detection of pellet agglomeration during Wurster coating [30], while SFV has recently been established for in-line particle size monitoring in fluidized bed granulation [27,[31][32][33][34][35][36]. The obtained SFV data improved the understanding of the impact of process variables by using model-based process control approaches, such as DoE, univariate and multivariate PLS.…”
Section: Introductionmentioning
confidence: 99%
“…However, particle size determination was influenced by size segregation in the fluid bed: the in-line technique underestimated and the at-line method overestimated the final granule size. Lipsanen et al showed that the pressure difference over the upper filters (indication of blockage of filters) and the fluidization parameter correlated well with the in-line particle size measurements [27].…”
Section: Spatial Filter Velocimetry (Sfv)mentioning
confidence: 91%
“…Furthermore, we examined whether the in-line particle size data could be related to off-line measured end granule properties (tapped density and Hausner ratio) using univariate, multivariate and multiway models, hence allowing early estimation of these end product properties during processing. Whereas previous reports about in-line SFV emphasized on the sensitivity of the technique towards the in-line detection of granule size and process failures [26][27], the present study examines the application of the technique to enhance fluidized bed process understanding through the continuous measurement of particle size, in combination with DOE. Furthermore, models were built using the continuously measured in-line particle size information allowing early prediction of end granule properties.…”
Section: Spatial Filter Velocimetry (Sfv)mentioning
confidence: 99%
“…It has been proposed in the literature that development of a robust fluid bed process depends on control of the moisture profile [23,24,[31][32][33][34][35][36][37][38][39][40]. Moisture profile control of a fluid bed granulation process requires an operator or controller to manipulate three interdependent control "levers" available during processing.…”
Section: Fluid Bed Granulation Modelingmentioning
confidence: 99%